From Cook to Flinders: The navigation of Torres Strait. (February 2015) - Morgan, Kenneth
This article offers the first published appraisal of the attempts by navigators to find a safe passage through Torres Strait, a notoriously difficult sea channel for sailing vessels. Securing such a passage was important for the timing and viability of commercial and naval ships following this route from the Pacific to the Indian Ocean. Luis Vaez de Torres' traversal of the strait that bears his name was kept secret for over a century and a half after his voyage in 1606. It was not until the late 1760s that a chart showing his track through Torres Strait was published. This article considers the routes followed by the small number of navigators who undertook the earliest known voyages through the strait: James Cook, William Bligh, William Wright Bampton and Matthew Flinders. The reasons why these navigators took different routes through Torres Strait are explained in relation to the cartographical knowledge they possessed. The navigational difficulties they encountered are explained. The article shows that knowledge of passages through the strait increased incrementally from one voyage to another. Cook sailed via Endeavour Strait, the most southerly passage through Torres Strait. Bligh followed a much more northerly passage to the north of Prince of Wales Island. Flinders took a course between that of Cook and Bligh to sail to the south of Prince of Wales Island. The article concludes that Flinders had the most thorough information with which to navigate Torres Strait, and that his passage became the preferred course for ships sailing between the north and Australia and the south of New Guinea by the mid-nineteenth century.